Fracture risk in oral glucocorticoid users: a Bayesian meta-regression leveraging control arms of osteoporosis clinical trials. Issue 5 (May 2016) - Amiche, M.; Albaum, J.; Tadrous, M.; Pechlivanoglou, P.; Lévesque, L.; Adachi, J.; Cadarette, S.
Abstract Summary Little data exist on the frequency of fracture among oral glucocorticoid users. We examined the effect of oral glucocorticoids on fracture incidence using data from randomized controlled trials. Patients starting glucocorticoids had a higher probability of fracture and decline in bone mineral density compared to chronic glucocorticoid users. Introduction Oral glucocorticoids (GCs) are the leading cause of secondary osteoporosis. However, there have been few studies that quantify the rate of fracture among GC users. We sought to provide a pooled estimate of fracture risk from randomized controlled trials (RCTs) of GC-treated patients. Methods We updated a MEDLINE search published by the American College of Rheumatology through to March 2015 and identified RCTs of osteoporosis therapies that reported fracture and bone mineral density (BMD) among oral GC users. We restricted the analysis to placebo or control arms. RCT arms were stratified by GC exposure at enrolment to GC initiators (≤6 months) and chronic GC users (>6 months). Bayesian meta-regression was used to estimate the annual probability of vertebral fracture (primary), non-vertebral fracture and percentage change in lumbar spine and femoral neck BMD. Results The annual incidence of vertebral and non-vertebral fracture was 5.1 % (95 % CrI = 2.8–8.2) and 2.5 % (95 % CrI = 1.2–-4.2) among GC initiators, and 3.2 % (95 % CrI = 1.8–5.0) and 3.0 % (95 % CrI = 0.8–5.9) among chronic GC users. Our meta-regression identified a non-significant effect of group-level variables (mean age, mean BMD, mean GC daily dose, patients with previous vertebral fractures, proportion of women and adjuvant used) on vertebral fracture rate. Conclusion Our study found higher vertebral fracture incidence among GC initiators, yet a relative decline in fracture incidence with longer exposure. Our findings suggest that fracture incidence among oral GC users may be more common than previously estimated. Optimizing GC-induced osteoporosis management during early exposure to GC is essential to prevent fractures.